PERAN KOMITE SEKOLAH DALAM PEMASARAN LEMBAGA PENDIDIKAN - Mulya, Nana; Nurmadiah, Nurmadiah (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2022)
The development of educational institutions is progressing rapidly. Not only in managing education such as managing learning methods, learning materials and student development activities, marketing activities of educational institutions to the wider community are also very important to pay attention to. One of the parties that plays a role in the marketing activities of educational institutions is the school committee. This study aims to determine the role of school committees in the marketing of educational institutions. The type of approach used is a descriptive qualitative approach with research subjects namely the principal, vice principal and school committee. The object of this research is the role of school committees in marketing educational institutions with research data obtained through observation and interviews. From the research carried out, it was found that the role of the school committee in the marketing of educational institutions is as a provider of considerations in planning the marketing of educational institutions, assisting in funding marketing activities, supervising the continuity of marketing activities, and connecting communication to the authorities, namely the government.